Structure of the Peptidoglycan Synthase Activator LpoP in Pseudomonas aeruginosa - Caveney, Nathanael A. (Structure, 2020)
Peptidoglycan (PG) is an essential component of the bacterial cell wall and is assembled from a lipid II precursor by glycosyltransferase and transpeptidase reactions catalyzed in particular by bifunctional class A penicillin-binding proteins (aPBPs). In the major clinical pathogen Pseudomonas aeruginosa, PBP1B is anchored within the cytoplasmic membrane but regulated by a bespoke outer membrane-localized lipoprotein known as LpoP. Here, we report the structure of LpoP, showing an extended N-terminal, flexible tether followed by a well-ordered C-terminal tandem-tetratricopeptide repeat domain. We show that LpoP stimulates both PBP1B transpeptidase and glycosyltransferase activities in vitro and interacts directly via its C terminus globular domain with the central UB2H domain of PBP1B. Contrary to the situation in E. coli, P. aeruginosa CpoB does not regulate PBP1B/LpoP in vitro. We propose a mechanism that helps to underscore similarities and differences in class A PBP activation across Gram-negative bacteria.